Co mówią zeznania? O dwóch powieściach kryminalnych Leo Belmonta ("Sprawa przy drzwiach zamkniętych" i "Pomiędzy sądem i sumieniem") = What does the testimony say? On two crime novels by Leo Belmont ("Sprawa przy drzwiach zamkniętych" and "Pomiędzy sądem i sumieniem") - Żmudziak, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article is an attempt to investigate the origins of the Polish crime fiction, which developed in the last years of the nineteenth century. A reflection on the evolution of the genre on the Polish soil, onthe absorption and imitation of foreign models of detective novel and on the first independent andfully conscious attempts of native artists to create its new version is accompanied by an analysis oftwo novel by Leo Belmont - "Sprawa przy drzwiach zamkniętych" and "Pomiędzy sądem i sumieniem".This analysis not only shows the original form of the first Polish courtroom drama with an intricatelogical structure of forensic investigation, but also offers the evidence for coming of age of the Polishauthors of this genre, as well as readers open to new reading experiences.
Keywords: Belmont, Leo (właśc. Blumental, Leopold; polski eseista, pisarz; 1865-1941); literatura polska - 19 w. - tematyka; powieść kryminalna